About sphingophilous Angiosperms in Brazil - Silberbauer-Gottsberger, Ilse; Gottsberger, Gerhard (Springer Nature, 1975)
In order to study the functional differentiation in flowers of 15 sphingophilous Brazilian Angiosperms, anthesis, flower morphology, flower odours and the behaviour of visiting animals were investigated. All 15 species were found to have nocturnal anthesis, but only 13 proved to be predominantly visited by hawk-moths. Of the 3 Lafoensia populations studied, one was pollinated only by hawk-moths, one was chiropterophilous and one had a mixed bat-moth pollination; there are corresponding differences in flower dimensions. © 1975 Springer-Verlag.
Keywords: Amaryllidaceae: Crinum; Apocynaceae: Macrosiphonia; Caesalpiniaceae: Bauhinia; Capparaceae: Capparis; Chrysobalanaceae: Couepia; Flower biology; Hillia; Liliaceae: Dracaena; Lythraceae: Lafoensia; Mimosaceae: Inga; Rubiaceae: Tocoyena; sphingophily in Brazil; Vochysiaceae: Qualea